VILLAGE GOVERNMENT IMPLEMENTATION BASED ON LAW NUMBER 6 OF 2014 - Budi Santoso; Arif Awangga (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
The purpose of this research is to find out how the village government functions in carrying out village autonomy. Based on Law no. 6 of 2014 concerning Village Autonomy and how the concept of village financial management is based on Law no. 6 of 2014 concerning Village Autonomy. This study uses normative legal research methods so that it can be concluded: 1. The government and BPD are village administrations that have a very important role in administering village governance. With the existence of Law Number 6 of 2014 in its implementation it reflects village genuine autonomy, democratization, participation and diversity as the foundation of village thinking. The village government is the village head and village apparatus as elements of village administration. Meanwhile, village officials consist of a village secretariat led by a village secretary, field technical implementers and regional elements adapted to the needs and conditions of the local region. 2. The concept of village finance is almost the same as the concept of state finance, carried out through the Village Revenue and Expenditure Budget mechanism, which consists of the village revenue, expenditure and financing sections, which are carried out by the Village Head and his apparatus which are discussed jointly with the Village Consultative Body. Village financial management has juridical implications for the Village Head and the Village Consultative Body to be able to compile, authorize, implement, supervise and be accountable for village financial management. If there is negligence or intentional action, it will result in accountability both administratively and criminally. Regency/City Governments are obliged to allocate a budget for village finances, as well as provide guidance and supervision.